The Use of Real-Time Polymerase Chain Reaction Combined with Specific-Species Primer for Analysis of Dog Meat DNA in Meatball - Abdul Rohman; Wiranti Sri Rahayu; Sudjadi Sudjadi; Sudibyo Martono (Universitas Gadjah Mada, 2021)
The presence of dog meat is a crucial issue because dog meat is non-halal meat for Muslims. The objective of this study was to design and validate species-specific primer for the identification of dog meat DNA in meatball using real-time polymerase chain reaction (real-time PCR). The specific primer targeting mitochondrial cytochrome c oxidase subunit 1 (CO1) was validated. The specific primers used were designed using Integrated DNA Technologies (IDT) software and subjected to NCBI BLAST procedure. The candidate primers were tested for specificity study using several DNAs from fresh meat of pork, chicken, beef, lamb, and rat. The method was also validated by determining several parameters of linearity, sensitivity, precision, and efficiency. The results showed that primer could amplify specifically DNA target at an optimized annealing temperature of 56.6 °C. The limit of detection (LoD) obtained was 5 ng DNA, corresponding to 2.5% of dog meat in a meatball. The repeatability evaluation, expressed with relative standard deviation (RSD), and efficiency value was in the acceptable range (RSD < 25% and efficiency (90–105%). This method was successfully used for the analysis of marketed samples. Real-time PCR can be used as a standard method in halal authentication analysis through DNA analysis.